3D Asthenopia in Horizontal Deviation. (May 2013) - Kim, Seung-Hyun; Suh, Young-Woo; Yun, Cheol-Min; Yoo, Eun-Joo; Yeom, Ji-Hyun; Cho, Yoonae A.
Abstract Purpose: This study was conducted to investigate the asthenopic symptoms in patients with exotropia and esotropia while watching stereoscopic 3D (S3D) television (TV). Methods: A total 77 subjects who more than 9 years of age were enrolled in this study. We divided them into three groups; Thirty-four patients with exodeviation (Exo group), 11 patients with esodeviation (Eso group) and 32 volunteers with normal binocular vision (control group). The S3D images were shown to all patients with S3D high-definition TV for a period of 20 min. Best corrected visual acuity, refractive errors, angle of strabismus, stereopsis test and history of strabismus surgery, were evaluated. After watching S3D TV for 20 min, a survey of subjective symptoms was conducted with a questionnaire to evaluate the degree of S3D perception and asthenopic symptoms such as headache, dizziness and ocular fatigue while watching 3D TV. Results: The mean amounts of deviation in the Exo group and Eso group were 11.2 PD and 7.73PD, respectively. Mean stereoacuity was 102.7 arc sec in the the Exo group and 1389.1 arc sec in the Eso group. In the control group, it was 41.9 arc sec. Twenty-nine patients in the Exo group showed excellent stereopsis (≤60 arc sec at near), but all 11 subjects of the Eso group showed 140 arc sec or worse and showed more decreased 3D perception than the Exo and the control group (p < 0.001, Kruskal–Wallis test). The Exo group reported more eye fatigue (p < 0.001, Kruskal–Wallis test) than the Eso and the control group. However, the scores of ocular fatigue in the patients who had undergone corrective surgery were less than in the patients who had not in the Exo group (p < 0.001, Kruskal–Wallis test) and the amount of exodeviation was not correlated with the asthenopic symptoms (dizziness, r = 0.034, p = 0.33; headache, r = 0.320, p = 0.119; eye fatigue, r = 0.135, p = 0.519, Spearman rank correlation test, respectively). Conclusion: Symptoms of 3D asthenopia were related to the presence of exodeviation but not to esodeviation. This may indicate that S3D symptoms are closely related to the convergence demand.